Case report: Isolated immunoglobulin G4-related sclerosing cholangitis misdiagnosed as hilar cholangiocarcinoma - Li, Hui; Wang, Ran; Wang, Dongyang; Tang, Yufu; Liu, Xuantong; Li, Hongyu; Qi, Xingshun (Frontiers in Oncology, 2024)
Background Immunoglobulin G4-related sclerosing cholangitis (IgG4-SC) is frequently accompanied with type 1 autoimmune pancreatitis (AIP). Isolated IgG4-SC which is not accompanied with AIP is uncommon in clinical practice, and its manifestations are similar to those of hilar cholangiocarcinoma. Case presentation A 55-year-old male presented with persistent aggravation of icteric sclera and skin. He was initially diagnosed with hilar cholangiocarcinoma and underwent surgery. However, positive IgG4 plasma cells were found in the surgical specimens. Thus, a pathological diagnosis of IgG4-SC was established. After that, steroid therapy was given and initially effective. But he was steroid dependent, and then received rituximab therapy twice. Unfortunately, the response to rituximab therapy was poor. Conclusion It is crucial to differentiate isolated IgG4-SC from hilar cholangiocarcinoma to avoid unnecessary surgery. Future studies should further explore effective treatment strategy in patients who do not respond to steroids therapy. It is also required to develop novel and accurate diagnostic approaches to avoid unnecessary surgical procedures.